The Study of Linguopoetics in Uzbek Linguistics - Ashurova Zulkhumor Shodiyevna; Ubaydullayev Bekhruz (International Journal on Integrated Education, 2022)
This article discusses the interest and study of linguopoetics in Uzbek linguistics, as well as such issues as the harmony of linguistic thinking, linguopoetical features of a work of art.